Biochemical characterization of a murein hydrolase induced by bacteriophage Dp-1 in Streptococcus pneumoniae: comparative study between bacteriophage-associated lysin and the host amidase. - García, P (1984)
A phage-associated lysin recently isolated and purified from Streptococcus pneumoniae infected with bacteriophage Dp-1 has been biochemically characterized as an endo-N-acetyl-muramyl-L-alanine amidase. The purified peptides obtained after treatment of the cell wall with phage-associated lysin are composed of glutamic acid, alanine, lysine, glycine, serine, and aspartic acid in the molar ratios of 1.0:1.6:1.0:1.0:0.8:0.6. The N-terminal amino acid of this peptide has been characterized as alanine. This amidase and the inactive form of the amidase (E form) previously purified (J.V. Höltje and A. Tomasz, J. Biol. Chem. 251:4199-4207, 1976) from S. pneumoniae differ in their molecular weights, as well as in their capacity to be stimulated by reducing agents, and do not cross-react immunologically, although anti-phage-associated lysin serum was able to recognize and inhibit both phage-associated lysin and the active form (C form) of the host amidase.